Translation Procedure Of Economic Term In A Textbook Entitled English For Economic By Hengki And Ratna - Fina Nurvita; Maria Dita Manggarrani (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2025)
This study aims to examine the translation procedures of economics terms in the textbook “English for Economics” by hengki and Ratna. In this study, the research collected 150 data points, which were subsequently analyzed using Peter Newmark translation procedures. The analysis revealed that the procedure of transference dominated the data, Transposition for 47 or 31.33%. The second Through-Translation, with 22 or 14.67%. The third was Recognized Translation with 20 or 13.33%. The fourth was Couplets with 18 or 12.00%. The fifth was Cultural Equivalent with 16 or 10.67%. The sixth was Descriptive Equivalent with 10 or 6.67%. The Seventh was Functional equivalent with 7 or 4.67%. The Eight was Modulation with 5 or 3.33%. The Ninth was Naturalization with 3 or 2%. Lastly, tenth and eleventh were Synonymy and Transference with 1 or 0.67%.